Reproducibility and Consistency of Isolation Protocols for Fibroblasts, Smooth Muscle Cells, and Epithelial Cells from the Human Vagina - Jayson Sueters; Rogier Schipperheijn; Judith Huirne; Theo Smit; Zeliha Guler (Cells)
(1) Background: For the reconstruction of a human vagina, various surgical procedures are available that are often associated with complications due to their failure to mimic the physiology of the human vagina. We recently developed a vascularized, organ-specific matrix from healthy human vaginal wall tissue with suitable biomechanical properties. A superior graft would require further extensive colonization with autologous vaginal cells to reduce complications upon implantation. However, reports on isolation of vaginal cells from biopsies are scarce, and published protocols rarely contain sufficient details. In this study, we aimed to examine protocols for inconsistencies and identify (where possible) the optimal protocol in terms of reproducibility and efficiency for isolation of human vaginal fibroblasts (FBs), epithelial cells (VECs), and smooth muscle cells (SMCs). Overall, this study aims to guide other researchers and aid future tissue engineering solutions that rely on autologous cells. (2) Methods: A total of 41 isolation protocols were tested: four protocols specific to FBs, 13 protocols for VECs, and 24 protocols for SMCs. Protocols were derived from published reports on cell isolation by enzymes, with exclusion criteria including the need for specialized equipment, surgical separation of tissue layers, or missing protocol details. Enzymatic digestion with collagenase-I, collagenase-IV, and dispase-II was used for isolation of VECs, collagenase-IV for isolation of SMCs, and collagenase-IA for isolation of FBs. Fluorescent immunostaining was applied to identify VECs with cytokeratin, SMCs with desmin, endothelial cells with UEA-1, and FBs with vimentin. Protocols were assessed based on (>95%) homogeneity, duplicate consistency, cell viability, and time to first passage. (3) Results: A total of 9 out of the 41 protocols resulted in isolation and expansion of vaginal FBs. This involved 1 out of 13 VEC protocols, 6 out of 24 SMC protocols, and 2 out of 2 FB protocols. Isolation of vaginal SMCs or VECs was not achieved. The best results were obtained after digestion with 0.1% collagenase-IV, where pure FB colonies formed with high cell viability. (4) Conclusions: Today, vaginoplasty is considered the gold standard for surgically creating a neovagina, despite its considerable drawbacks and limitations. Tissue-engineered solutions carry great potential as an alternative, but cell seeding is desired to prevent complications upon implantation of grafts. In this study, we examined isolation of human vaginal FBs, SMCs, and VECs, and identified the most efficient and reliable protocol for FBs. We further identified inconsistencies and irreproducible methods for isolation of VECs and SMCs. These findings aid the clinical translation of cell-based tissue engineering for the reconstruction and support of vaginas, fulfilling unmet medic needs.